Effect of non-performing loan and loan to deposit ratio on return on assets - Dede Hertina; Sofan Rahmat; Ahmad Furqon (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to determine the effect of Non-Performing Loans and Loan to Deposit Ratio on Return on Assets in commercial banks listed on the Indonesia Stock Exchange for the period 2014 - 2020. The research population was 44 banks, using purposive sampling, the research sample was obtained as many as 6 public banks listed on the Indonesia Stock Exchange for the period 2014 - 2020. This research method uses multiple linear regression analysis techniques. The results showed that the variables of Non-Performing Loan and Loan to Deposit Ratio had an effect on Return on Assets. This means that the bank has optimized the existing capital to be channeled through credit so that the bank's profit is maximized.